Ficção científica , cibercultura e pós-modernidade: velocidade e religião no discurso cinematográfico de David Cronenberg videodrome e eXistenZ - Góes, Maria das Graças Teixeira de Araújo (2007)
The research is devoted to the study of David Cronenberg s films Videodrome and eXistenZ. Both movies belong to the science fiction genre, which, in our times, has gained specific features, representing the present with futuristic connotations, due to the fact of technical innovations being inserted in every sector of society. By portraying the cultural context of their times by means of metaphorical narratives and bizarre and surreal images, the films lead us to an analysis of post-modernism, cyberculture and velocity as a sociohistorical process that is realized without a legitimating discourse. For the same reason, we are also led to reflect on the imaginary context that permeates the technological society, taking as its parameter the myth of the cyborg, arising from the coupling of man and machine, and also the mythical-religious discourse present in the movies s narratives, resulting from the socio-technological process that is always contaminated by the link between religion and science. David Cronenberg s two films reproduce a social configuration in which the transmission of images is processed by means of technologies of the sensory (in the case of Videodrome) and of intelligence (eXistenZ). It therefore became necessary to delve into the media culture, so as to identify the influences exerted by technological communication devices (live or online). In view of the various themes comprised in the study, it was necessary to undertake an extensive bibliographical study, as well as research on the Internet. Baudrillard, Kellner and McLuhan, among others, are authors who have produced important analyses of this culture. Lévy, Johnson and Lemos are some of the researchers who have written about cyberculture, a subject that finds in Rüdger and Trivinho its most organized and consummate critical vision. We have studied post-modernism based on the ideas of Harvey, Jameson and Kumar, among others. Regarding the research on dromocracy, two authors have merited our attention: Virilio, who launched the subject s theoretical basis, and Trivinho, who has built a critical reflexion on the neuralgic and specific points of the logic of velocity in cyberculture. Erick Felinto provided us with subsidies for an analysis of religion in the technological society. Aumont, Brissac, Deluzer, Gomes, Machado, Sodré and Todorov have been of great assistance in our reflection on cinema and science fiction; Haraway led us to a greater understanding of the man/machine coupling, and, finally, Peirce and Santaella were the theoretical foundation for our semiotic analysis